The application of driving fatigue detection and monitoring technologies in transportation sector: A review - Ibrahim, Muhammad Shafiq; Kamat, Seri Rahayu; Shamsuddin, Syamimi (Academia Industry Networks, 2023)
Driving fatigue is the leading cause of traffic accidents in many countries, prompting the development of a number of fatigue detection devices. This paper concisely reviews the existing fatigue detection system for transportation sectors. A rigorous systematic literature review (SLR) was utilized to find robust and high-potential material related to the research issue. According to the available literature research, many fatigue detection devices have been developed and commercialized, categorized into three groups based on the detection target's features: vehicle-based parameters, behaviour-based parameters and physiological-based parameters. However, currently available driver fatigue detection systems are divided into two categories: (i) very expensive systems that are limited to specific high-end automobile models and (ii) affordable alternatives for old and cheap vehicles that are not robust. Regardless of the physiological-based parameters' great accuracy in identifying driving fatigue, practically all available fatigue detection devices are classified as vehicle and driver behaviour-based parameters. As a result, this study looked into the use of physiological method in the future fatigue detection studies. The study's findings will help researchers, politicians, and practitioners create a system to significantly reduce road accidents and improve road safety.